2013
DOI: 10.1182/blood-2013-03-478255
|View full text |Cite
|
Sign up to set email alerts
|

Toward eliminating HLA class I expression to generate universal cells from allogeneic donors

Abstract: Key Points Allogeneic-donor–derived cells can be genetically modified to eliminate expression of HLA-A. HLA-A disruption from donor cells is a step toward generating allogeneic cells as an off-the-shelf therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
207
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(208 citation statements)
references
References 48 publications
1
207
0
Order By: Relevance
“…On the basis of these analyses, we conclude that TALEN-mediated genome editing can be incorporated into a large-scale T-cell culture process as a practical and safe approach to the manufacturing of third-party CAR T cells for use in adoptive T-cell immunotherapies. Zinc finger nucleases have previously been applied for gene editing in human T cells, including inactivation of both the TCRa and TCRb genes for enabling allogeneic "off-the-shelf" and TCR replacement strategies and inactivation of an HLA class I gene (34)(35)(36). Our observations, regarding the functional capabilities of TRAC KO T cells, are consistent with the results described in the aforementioned publications; T cells lacking a TCR component lose CD3 expression and all capacity for activation via either the TCR or through the CD3 complex.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these analyses, we conclude that TALEN-mediated genome editing can be incorporated into a large-scale T-cell culture process as a practical and safe approach to the manufacturing of third-party CAR T cells for use in adoptive T-cell immunotherapies. Zinc finger nucleases have previously been applied for gene editing in human T cells, including inactivation of both the TCRa and TCRb genes for enabling allogeneic "off-the-shelf" and TCR replacement strategies and inactivation of an HLA class I gene (34)(35)(36). Our observations, regarding the functional capabilities of TRAC KO T cells, are consistent with the results described in the aforementioned publications; T cells lacking a TCR component lose CD3 expression and all capacity for activation via either the TCR or through the CD3 complex.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent report demonstrated that reconstitution of NKTs in peripheral blood is associated with long-term remission in pediatric leukemia patients receiving haploidentical stem cell transplantation (71,72). Hence, unlike donor-derived CAR-T cells, CAR-NKTs can be given early after HSCT when the disease burden is minimal and the curative potential of immunotherapy jci.org Volume 126 Number 6 June 2016 system as previously described (76). A clone with an intermediate level of CD1d expression induced the highest rate of NKT proliferation and was further modified with lentiviral vectors encoding CD86, 4-1BBL, or OX40L followed by single cell sorting and clonal expansion.…”
Section: Nkt Isolation Transduction Expansion and Sortingmentioning
confidence: 99%
“…We rendered K562 cells HLA null by eliminating the HLA-C gene from the K562 cell genome using an HLA-Cspecific ZFN as previously described (76). Briefly, ZFNs containing 5 or 6 fingers were designed and assembled using an established archive of prevalidated 2-finger and 1-finger modules (Sangamo BioScience).…”
Section: Author Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding applicability of engineered T cells, strategies are being developed to generate "universal" T cells that could be manufactured from one donor and administered to multiple patients. For instance, this could be done by eliminating the expression of endogenous TCR to generate T cells devoid of alloreactive TCRs (27). Finally, ACT efficacy may be improved by generating and/or selecting T cells with enhanced proliferative and antitumor capacity.…”
Section: Tcr T Cells Some On-target Toxicities Have Been Observed Wimentioning
confidence: 99%